Energy Transition and Climate Change in Decision-making Processes - Tsantopoulos, Georgios; Karasmanaki, Evangelia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is a growing concern about the climate; numerous voices stress that, in order to overcome the climate crisis, the transition to a low-carbon society is the most reasonable path to follow. In this type of society, individuals would be characterized by making mindful efforts to drastically decrease carbon and greenhouse gas emissions, and promote benign energy sources. In order to facilitate this transition, a social perspective in addition to technological, political and economic aspects must be integrated into the relevant decision-making processes. This is necessary because the public can strongly affect actions aimed at driving profound changes in traditional energy systems. To contribute to the effort of promoting energy transition, the Editors of this book invited scholars and practitioners conducting research in the areas of climate change and the energy transition to submit their work. This book includes studies that establish a valuable source of information which can be used to enhance decision-making processes which, in turn, can turn the energy transition into reality. Hopefully, efforts such as this collection of knowledge can help economies make a step towards a secure and sustainable energy future in which renewables will have replaced the centuries-long human dependence on fossil fuels.